PENGARUH PERILAKU TERHADAP KEPATUHAN MASYARAKAT MENGGUNAKAN MASKER DI KABUPATEN ENDE - Sekunda, Maria S.; Budiana, Irwan; Cahyani , Sisilia L.; Kurnia, Theresia A. (Poltekkes Kemenkes Kupang, 2023)
The existence of regulations from the government regarding the COVID-19 health protocol does not immediately reflect changes in people's behavior. There are people who do not wear masks when they are outside the house. There are also those who use cloth masks and there IS a small number who wear medical masks of various types. This study aims to identify the factors that influence community compliance with using masks. This research is a correlational non-experimental study with a cross- sectional approach. The sample in this study was people who met the inclusion criteria, such as those aged between 20-65 years, living in the sub-district of Ende Tengah > 1 year, and willing to be studied with a purposive sampling technique. There are 2 data analyses carried out in this study, namely descriptive analysis which is used to determine the frequency of each respondent. Meanwhile, to determine the relationship between the independent variable and the dependent variable, bivariate analysis, and multivariate analysis were used using a logistic regression test. The results of the bivariate analysis show that the variables that affect people's compliance with using masks are the knowledge variable with an OR value of 1.6; p = 0.000; 95% CI = 1.054-6.401) and behavioral variables with an OR value of 9.96; p = 0.005; 95% CI = 1.52-10.33). The results of multivariate analysis showed that the behavioral variable was very significant with respondents' compliance in using masks (OR 2.67; p = 0.007; 95% CI = 1.32-5.42). Compliance and community behavior have an influence on compliance with using masks in preventing the transmission of Covid 19.